Clinical Presentations and Comparative Outcomes of Delayed-Onset Low-Grade Endophthalmitis Managed with or Without Intraocular Lens Explantation - Dave VP (Dove Medical Press, 2020)
Vivek Pravin Dave,1 Deepika C Parmeshwarappa,1 Avantika Dogra,1 Rajeev Reddy Pappuru,1 Avinash Pathengay,2 Joveeta Joseph,3 Taraprasad Das1 1Smt. Kanuri Santhamma Center for Vitreoretinal Diseases, Kallam Anji Reddy Campus, LV Prasad Eye Institute, Hyderabad, India; 2Retina and Uveitis Service, GMR Varalakshmi Campus, LV Prasad Eye Institute, Visakhapatnam, India; 3Jhaveri Microbiology Center, LV Prasad Eye Institute, Hyderabad, IndiaCorrespondence: Vivek Pravin DaveSmt. Kanuri Santhamma Center for Vitreoretinal Diseases, Kallam Anji Reddy Campus, LV Prasad Eye Institute, Hyderabad, IndiaEmail vivekoperates@yahoo.co.inPurpose: To compare the outcomes of delayed-onset low-grade endophthalmitis managed with and without intraocular lens (IOL) explantation.Setting: Tertiary eye-care research institute in southern India.Design: Retrospective comparative case series.Methods: The study included all cases of post-cataract surgery delayed-onset endophthalmitis from January 1990 to January 2019. Time to endophthalmitis, duration of symptoms, presenting visual acuity, time to IOL explantation when performed, resolution after explantation, number of intravitreal injections, and final visual acuity were compared in the IOL non-explanted and IOL explanted groups.Results: There were 115 eyes – 61 eyes in the IOL non-explant and 54 eyes in the IOL explant group. Between the two groups there was no statistically significant difference in age (58.37 ±  14.05 and 56.04 ±  14.96 years, respectively; p=0.35), vision at presentation (> 20/400 in 29.5% and 29.6% eyes, respectively; p=0.98), and the duration of follow-up (14.38 ±  16.05, median 8.5 months and 7.06 ±  3.55, median 6 months respectively; p=0.43). There was a statistically significant difference between the IOL non-explant and IOL-explant groups in the time to resolution of inflammation (92.70 ±  36.28 and 45.33± 11.2 days, respectively; p < 0.0001) and the number of intravitreal injections (4.57 ±  0.75, median 5 and 2.79± 2.11, median 2 respectively, p=0.005). Persistent/recurrent inflammation at 6 months was recorded in 18.03% and 5.55% in the IOL non-explant and IOL explant eyes, respectively (p=0.04). Favorable functional outcome was seen in 50.81% vs 68.51% in IOL non-explant and explant eyes, respectively (p=0.05).Conclusion: IOL explantation in delayed-onset endophthalmitis helps in earlier resolution of inflammation, need for lesser number of intravitreal injections and a trend towards better functional outcomes.Keywords: intraocular lens explantation, endophthalmitis, IOL, delayed-onset endophthalmitis, low-grade endophthalmitis